What can we learn about economics from sport during Covid-19? - Bryson, A.; Dolton, P.; Reade, J. J.; Schreyer, D.; Singleton, C. (Discussion paper 2021-01, 2021)
The economics of sport and how sport provides insights into economics have experienced exogenous shocks from Covid-19, facilitating many natural experiments. These have provided partial answers to questions of: how airborne viruses may spread in crowds; how crowds respond to the risk and information about infection; how the absence of crowds may affect social pressure and arbitration decisions; and how quickly betting markets respond to new information. We review this evidence and advise how sports economics research could continue to be most valuable to policymakers.